Chemical profiling and quantification of Tanreqing injection, a systematic quality control strategy equipped with UPLC-Q-Orbitrap fusion MS. Issue 7 (8th May 2020) - Feng, Su-Xiang; Zhang, Hao-Jie; Zhao, Di; Li, Rong-Rong; Du, Xue-Hang; Wang, Pei-Yang; Shu, Sheng-Nan; Qu, Ling-Bo; Li, Jian-Sheng
Abstract: Tanreqing injection is a Chinese medical formula used to treatment of respiratory diseases. In our study, we developed a feasible and accurate strategy applying an ultra-high-performance liquid chromatography coupled with Q Exactive™ Plus-Orbitrap Fusion mass spectrometers (UPLC-Q-Orbitrap Fusion MS/MS) to clarify and quantify the chemical profiling of Tanreqing injection rapidly. A total of 80 ingredients were identified by comparing the accurate mass, fragment ions, and cleavage pathways, including flavonoids, phenyl propionic acid, coumarins, amino acids, cholesterol, etc. And 18 characteristic components among them were definitely identified by comparison with reference substance. Meanwhile, the 18 representative constituents were simultaneously measured in eight batches Tanreqing injection utilizing UPLC-Q-Orbitrap Fusion MS/MS in negative ion mode. Among the 18 components, beta-d-glucopyranosiduronic acid, baicalin, ursodeoxycholic acid, and chenodeoxycholic acid were the predominant constituents. In principal components analysis results, five dominating components were extracted, and the variant contribution rates were ranked as: 37.86, 22.86, 16.42, 9.80, 7.32%, with the accumulated value 94.26%. 5-caffeoylquinic acid, isochlorogenic acid C, and baicalin possessed larger loads on the first factor. Our research carried out qualitative and quantitative analysis on Tanreqing injection, provided a certain reference for the research on pharmacodynamic material basis and the selection of quality markers. Graphical Abstract: